2018
DOI: 10.1111/nep.13179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of haemodialysis and residual renal function on serum levels of galectin‐3, B‐type natriuretic peptides and cardiac troponin T

Abstract: Plasma concentration of galectin-3 is reduced by the haemodialysis procedure. Lower RRF and urine volume are strongly associated with higher levels of galectin-3 and NT-Pro-BNP. These associations are important to the clinical interpretation of these biomarker levels in haemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…When looking at both corrected and uncorrected estimates, three estimates are based on LF-HD 4,16,20 and all report an increase in hs-cTnT after HD. Six estimates (corrected and uncorrected) are available for HF-HD 5,[14][15][16]18 and they range from À16% to 12%. However, one uncorrected estimate 14 are based on patients with a large UF (mean 2.7 L at baseline), increasing the effect from hemoconcentration due to UF.…”
Section: Discussionmentioning
confidence: 99%
“…When looking at both corrected and uncorrected estimates, three estimates are based on LF-HD 4,16,20 and all report an increase in hs-cTnT after HD. Six estimates (corrected and uncorrected) are available for HF-HD 5,[14][15][16]18 and they range from À16% to 12%. However, one uncorrected estimate 14 are based on patients with a large UF (mean 2.7 L at baseline), increasing the effect from hemoconcentration due to UF.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all maintenance HD patients were Asian in the present study, thus the generalizability of the study findings across ethnicities remains unclear. Third, due to the unavailability of data, several traditional and non-traditional risk factors for CV death, such as serum high sensitivity C-reactive protein, smoking, nutritional parameters and residual renal function or urine volume [ 37 ], were not adjusted in multivariable models. Therefore, as with other studies, our study may be limited by residual confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the levels of this protein correlate with the glomerular filtration rate in patients with a cirrhosis of the liver [ 31 ] or polycystic ovary [ 32 ]. High concentrations of galectin-3 in plasma have been associated with a risk of chronic kidney disease and are reduced using hemodialysis treatments [ 33 , 34 , 35 ]. It has been reported that an increase in the circulating concentration of galectin-3 (as can be observed in some inflammatory diseases) precedes the decrease in glomerular filtration.…”
Section: Discussionmentioning
confidence: 99%